Metabolism, pharmacokinetics, and bioavailability of cannabigerol in horses following intravenous and oral administration with micellar and oil formulations - Serrano-Rodríguez, Juan Manuel; Miraz, Raquel; Saitua, Aritz; Díez de Castro, Elisa; Ledesma-Escobar, Carlos; Ferreiro-Vera, Carlos; Priego-Capote, Feliciano; Sánchez de Medina, Verónica; Sánchez de Medina, Antonia (Frontiers in Veterinary Science, 2025)
IntroductionCannabigerol (CBG) is a non-psychoactive cannabinoid with growing interest in veterinary medicine; however, its pharmacokinetic profile in horses remains unknown. Understanding its absorption, distribution, metabolism, and elimination is essential to optimizing dosing strategies and evaluating its potential for clinical use in equine patients.MethodsA prospective crossover study was conducted in eight healthy adult horses to assess the in vivo metabolism and the pharmacokinetics after intravenous (IV) administration at 1 mg/kg and oral administrations at 10 mg/kg with two formulations (micellar and oil). Plasma concentrations of CBG and its main metabolite, CBG-glucuronide (CBG-G), were analyzed by LC-MSMS and modeled using a non-linear mixed effects model with MonolixSuite®. The model estimated the bioavailability, metabolic conversion, and absorption parameters. Furthermore, Monte Carlo simulations were performed to predict and evaluate the drug exposure after a multiple-dose regimen.ResultsHigh in vivo metabolism was observed with the formation of epoxy and hydroxy metabolites via phase I reactions, and CBG-G was the main metabolite from phase II reactions (75% of biotransformation). After IV administration, CBG showed a high volume of distribution (Vss = 74 L/kg) and systemic clearance (Cl = 1.67 L/h/kg), with a terminal half-life of approximately 29 h. The oral bioavailability was estimated at 28% between formulations, and an extensive presystemic metabolism was obtained with metabolite/parent AUC ratios exceeding 50. The micellar formulation showed a shorter time to achieve maximum concentration (Tmax) and faster absorption as compared to the oil formulation. The Monte Carlo simulations of multiple oral doses (10 mg/kg q24 h for 14 days) predicted differences between formulations. No adverse clinical effects were observed during the study.DiscussionThis study shows the first evaluation of the in vivo metabolism and pharmacokinetics of CBG in horses after IV and oral administration. The findings highlight extensive metabolite formation with significant glucuronidation, a large distribution volume, and high clearance. While both oral formulations produced similar systemic exposure, the faster absorption with the micellar formulation may inform clinical decisions depending on therapeutic goals. These data support the potential use of CBG in horses and offer a foundation for further studies in equine medicine.